ANALYSIS OF THE FACTORS AFFECTING THE QUALITY OF THE CHEMICAL AND MICROBIOLOGICAL DRINKING WATER AT THE DEPOT DRINKING WATER REFILL TULUNGAGUNG DISTRICT - Eka Puspitasari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2017)
Refill drinking water Depot is an industry that does the processing of the raw water into drinking water and sell directly to the consumer. Mn metal and bacterial Coliform is an indicator of refill drinking water polluters. This research aims to find the factors influencing the quality of Microbiology and chemistry at the depot drinking water drinking water refill Tulungagung district. Research using survey method with Cross sectional approach is analytical. The sampling technique used was Simple Random Sampling with a sample of 89 depot drinking water refill. Technique of data analysis using Regression and Logistic regression test linear. Independent variable examined was the source of raw water, the depot operator hygiene of drinking water, hygiene, sanitation, which covers three aspects namely sanitary location, building and facility sanitation. The results showed from 89 depot examined known as much as 79.8% sanitation facilities are not qualified, the value of the MPN 59.55% of eligible and levels of Mn 100% qualified. From Regresilogistik test results between independent variable with the value of the MPN indicate significance of 0.008 < (α = 0.05) on sanitation facilities are variable. This means there are influences between facilities sanitation microbiological quality of drinking water. On Linear regression test results between independent variable with the value obtained significance levels of Mn 0.47 > ((α = 0.05) which means no influence between independent variables with the chemical quality of drinking water. The lack of sanitation facilities increases the potential for bacterial contamination through the operator. Therefore the availability of on-site sanitation depot drinking water is a major factor that affects the quality of drinking water microbiology refills.